Iron(III) Chloride Promoted Oxidative Radical Cyclization for the Synthesis of Lactams Having a Quaternary Carbon - Yoshioka, Eito; Imoto, Yuuki; Yoshikawa, Tomohiro; Kohtani, Shigeru; Miyabe, Hideto (Synlett, 2017)
The oxidative radical cyclization of active methylene derivatives containing allyl groups as radical acceptors proceeded with the use of FeCl3 as a mild oxidant. The FeCl3-promoted cyclization reactions of α-substituted active methylene compounds provide a synthetic approach to various γ-lactams containing a quaternary carbon atom.
Keywords: radical reactions; oxidation; cyclization; ferric chloride; lactams